Camera Trap Study on Melanistic Leopard Population in Kali Tiger Reserve - Srinivasulu; Kamat, S. D. (Indian Forester, 2016)
Animal monitoring is the key tool in the hands of park managers to effectively manage the forests and wildlife. Advances in the field of Wildlife science provide scope in this regard. Elusive Melanistic leopards or Black Panthers are more commonly found in the Dandeli-Anshi Tiger Reserve (Now renamed as Kali Tiger Reserve) as compared to other protected areas of Karnataka. Camera trap survey was conducted in the forest ranges of Kulgi, Phansoli, Gund and Anshi during January to June 2015. In this study an effort has been made to estimate the percentage of melanistic individuals in total leopard population. 94 pairs of Camera traps were placed covering 763 Km2 area for 49 days in two blocks. Based on the image data the percentage of Melanistic animals in total leopard population has been derived.